Wolbachia Infections of Phlebotomine Sand Flies (Diptera: Psychodidae). Issue 2 (30th September 2014) - Ono, Midori; Braig, Henk R.; Munstermann, Leonard E.; Ferro, Cristina; O'NeilL, Scott L.
Abstract : Old and New World phlebotomine sand fly species were screened for infection with Wolbachia, intracellular bacterial endosymbionts found in many arthropods and filarial nematodes. Of 53 samples representing 15 species, nine samples of four species were found positive for Wolbachia by polymerase chain reaction amplification using primers for the Wolbachia surface protein ( wsp ) gene. Five of the wsp gene fragments from four species were cloned, sequenced, and used for phylogenetic analysis. These wsp sequences were placed in three different clades within the arthropod associated Wolbachia (groups A and B), suggesting that Wolbachia has infected sand flies on more than one occasion. Two distantly related sand fly species, Lutzomyia ( Psanthyromyia ) shannoni (Dyar) and Lutzomyia ( Nyssomyia ) whitmani (Antunes & Coutinho), infected with an identical Wolbachia strain suggest a very recent horizontal transmission.